Strategi Peningkatan Kinerja DC Microgrid dengan Konfigurasi DC/AC Coupling - Adhi Kusmantoro; Ardyono Priyadi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2023)
DC microgrid is a good solution for increasing demand for electricity loads and is an effective way to utilize renewable energy sources into distributed generation systems. Solar energy has intermittent properties when DC microgrids are used. In the previous research, the battery was used as an energy reserve to overcome fluctuations in the output power of photovoltaic (PV) arrays. However, the use of many batteries requires a high cost. This study aims to reduce power fluctuations on the DC bus, when the DC microgrid source from the PV array and battery is disconnected. The research method was carried out using MATLAB simulations, by designing a DC/AC coupling hybrid configuration. This configuration used two PV arrays, two multi-battery sources, and a utility network. DC microgrid settings were done separately by each converter by sending a reference signal to the converter control. In the first condition, the DC load and AC load were supplied from the PV array. In the second condition, the load was supplied from the battery. Meanwhile, in the third condition, the load was supplied from the utility network. The results showed that when using a PV array source, the DC bus voltage remained stable at 48 V, even though there was a spike at 08.00 and 15.00. Likewise, when using a battery source and utility network, the DC bus voltage was maintained at a level of 48 V. In this study, the DC microgrid was able to supply the load uninterruptedly using three conditions or modes. Therefore, the DC microgrid hybrid configuration can provide continuous electric power.